The Cambridge handbook on the sustainable development goals and international law / edited by Jonas Ebbesson, Stockholms Universitet, Ellen Hey, Erasmus Universiteit Rotterdam. - Ebbesson, Jonas; Hey, Ellen (Cambridge Law Handbooks., 2022)
In 2015, the United Nations established seventeen Sustainable Development Goals (SDG) that aimed 'to achieve a better and more sustainable future for all' by 2030. The chapters within this collection address each of these SDGs, considering how they relate to one another and international law, and what institutions could aid their implementation. Development has been a contentious topic since the decolonization period after World War II, and issues surrounding sustainable development are necessarily impacted by the multifaceted relationship between the Global South and Global North. Confronting the context and challenge of sustainable development, this collection outlines how the international economic system problematizes the attainment of the SDGs. Introducing a novel, cosmopolitan approach, this book offers new ways of understanding sustainable development and suggests potential solutions so that we might finally achieve it.